A Critique on Dimensions of Resistance Economy in Oil Industry - Farhad Tarahomi; Ali Asqar Esfandiary (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The content of the book "Dimensions of the Resistance Economics in the Oil Industry" includes the text of the general policies of the resistance economy, the correspondences and statements made in this regard, the history of the oil industry, and the actions taken by the Ministry of Oil in the pursuit of a resistive economy. Meanwhile, an attempt has been made to define a resistance economy in line with Islamic economics although it cannot be proven. The structure of the book is news-based and disquisition-based and has not been used sufficiently from scientific sources. Therefore, there is no analysis of the relationship between the resistance economy and the oil sector. The above work is applicable to general information on resistance policies and some of the Ministry of Oil's programs in this area, and, despite the authors' views, it is not a complete reference in this field. In this regard, it has been attempted to briefly explain the axes related to the crude oil and natural gas sectors in line with the resistance economy and identify the strengths and weaknesses. The analysis included cases to which the book did not refer and could be used as an introduction to future research.